Pattern of Complications and Their Predictors Following Transurethral Resection of the Prostate Using the Modified Clavien Classification System - Islam, Mohammad Manirul; Chowdhury, Md Golam Mowla; Islam, Md Faisal; Khan, Sarforaj Ali; Rahman, Hamudur; Rahman, Ashraf (Bangladesh Journal of Urology, 2025)
Background: Benign prostatic enlargement (BPE) is a common problem of ageing male, and its surgical management constitutes significantly to the urological workload. Although transurethral resection of the prostate (TURP) is the gold standard surgical treatment for BPE, it is not without complications. Previously, there was no consensus on how to define complications. This made the comparison of different reported series unreliable and has highlighted the fact that standardized methods in reporting data on surgical complications or morbidity are needed. In 1992, Clavien and his colleagues presented guidelines on the classification of complications of surgery on the basis of severity grading. In 2004, it was modified by Dindo, Demartines and Clavien to increase the accuracy and applicability of the CCS. Although modified Clavien classification system (MCCS) was proposed to grade complications of general surgery, its application in other branches of surgery as well as urology has been initiated recently. Objective: This prospective observational study was designed to observe the pattern of complications and their predictors following TURP using the modified Clavien classification system. Method: One hundred and fifteen patients with benign prostatic hyperplasia submitted to monopolar TURP from April 2016 to March 2017 in department of urology, BSMMU, were evaluated for complications occurring up to the end of the first postoperative month. All complications were classified according to the modified CCS. If multiple complications per patient occurred, categorization was done in more than one grade. Negative outcomes such as mild dysuria during this early postoperative period or retrograde ejaculation were considered sequelae and were not recorded as complications. Result: Overall complication rate was 22.6%. In this study more than half (60.6%) of the complications were grade I (20 out of 33 complications). Grade II complications were 33.33 % (11 out of 33 complications), Higher grade complications were scarce, both grade IIIa and IVa complications were 3.03% (1 complications for each grade out of 33 complications). There was no grade V complication in this study. Conclusion: Higher prostate volume, lower preoperative hemoglobin level, higher resected volume and longer resection time were the predictors of post-operative complications following TURP. Bangladesh J. Urol. 2024; 27(2): 115-124